Electronic design automation [1999 technology analysis and forecast]. - Martin, B.
This article presents an electronic design automation technology analysis and forecast for 1999. The subjects covered include: IC design moving to a higher level of abstraction; IC design reuse; and hardware/software integration
Keywords: AD 1999.; IC design; Abstraction level; Design reuse; Electronic design automation technology; Hardware/software integration; Technology analysis; Technology forecast